Bilateral versus Single Internal Mammary CABG: One-Year Results from the ART Trial - Sinclair, Heather Q. (MD Conference Express, 2010)
The use of bilateral internal mammary artery (BIMA) grafting is safe according to one-year data from the Arterial Revascularization [ART] Trial. One-year analyses focused on the safety and feasibility of this interventional approach.